Evaluation of acupuncture treatments of postpartum female pelvic floor dysfunction by four-dimensional transperineal pelvic floor ultrasound. Issue 42 (22nd October 2021) - Yao, Liping; Li, Fengzhi; Wang, Dandan; Sheng, Shaoqin
Abstract: Introduction: In the present investigation, a systematic evaluation of the clinical treatment performance of diagnosed with pelvic floor dysfunction is explored. By comparing the 4Dtransperineal pelvic floor ultrasound images with the acupuncture treatment performance of the patients, an evaluation system with various parameters is established to provide critical information to guide the clinical treatment fpostpartum female pelvic floor dysfunction (FPFD). Methods: Eighty patients diagnosed with FPFD are divided into 2 groups. After the designated treatment to the patients, they are carefully examined using transperineal pelvic floor ultrasound. The shape and activity of bladder neck, cervix and rectum anal canal under resting, anal sphincter and Valsalva movements are observed and recorded. The morphology and continuous shape of levator ani muscle in different states after 4D image reconstruction are obtained. Results: After the acupuncture treatment, the bladder neck descent is decreased by 3.8 cm and the anal levator muscle area is decreased by 3.4 cm 2 comparing with the control group. The anal levator muscle hole diameter is decreased by 0.3 cm, while the anterior and posterior diameter is reduced by 0.5 cm. Reduced possibility of cystocele and uterine prolapse is demonstrated by X 2 test. These changes upon acupuncture therapy are in line with the improved conditions of the patients, indicating these parameters can help evaluate the therapy performance. Conclusion: 4D pelvic floor ultrasound imaging provides objective and quantified information for the clinical diagnosis and treatment of FPFD and the assessment of therapy efficacy, making it a promising novel method in practical applications.